A comprehensive review on multi-physics modeling of photovoltaic modules. (15th April 2022) - Siddiqui, M.U.; Siddiqui, Osman K.; Alquaity, Awad B.S.; Ali, Haider; Arif, A.F.M.; Zubair, Syed M.
Graphical abstract: Highlights: A review is presented on various aspects of photovoltaic mathematical modeling. Radiation, optical, thermal, electrical, and structural models are included. Exergo-economic analysis of PV systems has been discussed. Future directions for these models are also presented. Abstract: The global photovoltaic capacity increased to around 760 GW in 2020, with a year-on-year increase of about 139 GW from 2019. As new photovoltaic systems continue to grow, there is a need for better and more reliable mathematical models to predict the performance of these systems. This article presents a comprehensive review of mathematical models for predicting the overall performance of photovoltaic devices, including their optical, thermal, electrical, and structural performance, as well as their exergo-economic analysis. The importance and significance of various aspects of these multi-physics models are highlighted, along with the future directions for improving the reliability and practical use of these models for design, performance evaluation, and optimization of such systems.